Preparation method of modified phosphogypsum base material for road engineering
Patent Information
- Application Number
- CN202610196663.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-02-11
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种道路工程用改性磷石膏基层材料的制备方法,解决了现有磷石膏基道路基层材料受磷、氟及有机杂质干扰导致胶凝材料水化迟滞、早期强度低、水稳定性差,且常规化学激发手段难以兼顾杂质固化与矿渣潜在活性的深度激发,导致材料施工可控性差及耐久性不足的技术问题
1、本发明通过生石灰水化释放化学能构建高温强碱反应场,在锰离子催化下将磷石膏中可溶性磷氟杂质原位转化为难溶性铁络合物沉淀,实现了杂质深度矿化与胶凝材料网络重构,明显提高了基层材料的水稳定性与力学性能,现有技术多采用物理掺合水泥或常温碱激发,往往存在杂质屏蔽效应强、界面粘结力弱的缺陷,本方案有效解决了传统改性材料早期强度发展缓慢及后期易泛霜的难题。
Smart Images

Figure CN122079517B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of road engineering materials technology, specifically a method for preparing a modified phosphogypsum base material for road engineering. Background Technology
[0002] Phosphogypsum, a solid waste product from the phosphate fertilizer industry, generates a massive annual output that is difficult to store and dispose of. It not only occupies significant land resources but also poses a risk of polluting groundwater and soil. Utilizing it in road engineering to prepare road base materials is currently one of the main ways to dispose of this industrial byproduct. If properly processed, this material can replace traditional road construction materials such as crushed stone and lime-soil, and can be laid under asphalt or cement concrete layers to bear the main vehicle load, which is of practical significance for reducing project costs and protecting the environment.
[0003] In existing technologies, cement, lime, or fly ash are commonly used as cementing materials to stabilize phosphogypsum. Through physical mixing, the loose phosphogypsum particles are bound together using the hydration of cement or the pozzolanic effect of lime. This cold-mix process is relatively simple, requiring no complex heating equipment and can be applied at room temperature. After a certain curing period, the solidified material possesses a certain compressive strength and slab-like structure, basically meeting the initial strength requirements of base course materials for general-grade roads.
[0004] However, simple cold-mix processes often fail to completely shield the soluble phosphorus, fluorine, and organic impurities in phosphogypsum. These impurities easily adsorb onto the surface of the cementitious material, forming a dense film that blocks the hydration reaction channels, resulting in excessively long setting time, slow early strength development, and poor water resistance. Slag powder added to improve later strength is difficult to deagglomerate quickly at room temperature and in weakly alkaline environments due to its dense glassy surface structure, thus its potential activity cannot be fully realized. Although attempts have been made to increase the amount of quicklime to utilize its heat of hydration to activate activity, this heat release is often difficult to control precisely, easily causing localized overheating leading to rapid moisture evaporation, false setting of the mixture, and even uneven calcium oxide digestion causing later volume expansion and cracking. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing modified phosphogypsum base materials for road engineering. This method solves the technical problems of existing phosphogypsum-based road base materials, which suffer from delayed hydration of cementitious materials, low early strength, and poor water stability due to interference from phosphorus, fluorine, and organic impurities. Furthermore, conventional chemical activation methods are insufficient to simultaneously achieve the deep activation of impurity solidification and the potential activity of slag, resulting in poor controllability and insufficient durability of the materials during construction.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a modified phosphogypsum base material for road engineering includes the following steps: S1. Mix aged phosphogypsum with ferrous sulfate heptahydrate, sodium fluorosilicate and manganese sulfate monohydrate, and use the water in the phosphogypsum to dissolve the salts to form an acidic slurry. S2. Add heat-curing dry powder to the slurry obtained in S1 and perform high-speed shear mixing. Use the heat released by the hydration of the heat-curing dry powder to raise the slurry temperature to 65℃-85℃, creating a high-temperature strong alkaline environment to initiate the manganese catalytic oxidation reaction and thermal etching of the slag. S3. Immediately after the S2 reaction is completed, a rapid cooling conditioning liquid is injected into the mixer under high pressure. The latent heat of water evaporation is used to rapidly reduce the temperature of the slurry to below 45°C, thus completing the rapid cooling quenching and slow setting lock. S4. Discharge and age the mixture to obtain the modified phosphogypsum base material.
[0007] By adopting the above technical solution, this invention constructs a modification process system based on "acidic dissociation-thermochemical excitation-phase change temperature control". Specifically, in the initial stage of mixing, the attached water of phosphogypsum itself dissolves ferrous sulfate heptahydrate, sodium fluorosilicate, and manganese sulfate monohydrate. The resulting acidic liquid environment helps to peel off the insoluble eutectic phosphorus and fluorine impurities attached to the surface of gypsum dihydrate crystals, allowing ferrous ions and manganese ions to be uniformly adsorbed at the particle interface, providing precursors for subsequent reactions.
[0008] Subsequently, heat-cured dry powder is added and subjected to high-speed shearing. This step, through the rapid hydration of highly active calcium oxide, releases a large amount of chemical energy in a short time, causing the reaction system temperature to rise sharply to over 65°C. This in-situ generated thermal effect, combined with the high alkalinity of the system, significantly accelerates the hydrolysis process of sodium fluorosilicate. The generated active hydrogen fluoride reacts with OH-... - The synergistic effect allows for deep thermal etching of the glassy structure on the surface of slag powder, disrupting the Si-O and Al-O bonds and exposing highly active reaction sites. Simultaneously, the high-temperature environment significantly lowers the activation energy of the redox reaction. Under the catalysis of manganese ions, ferrous ions rapidly transform into trivalent ferric hydroxide colloids with a high specific surface area, which then adsorb and complex with dissolved phosphate, fluoride ions, and organic acids, resulting in the mineralization and fixation of impurities accompanied by a change in slurry color.
[0009] The rapid cooling conditioning liquid introduced in the later stage of the reaction plays a role in terminating and regulating the reaction. The atomized droplets instantly vaporize upon contact with the high-temperature slurry, utilizing the latent heat of vaporization of water to dissipate excess heat and prevent false coagulation or microcracks caused by sustained high temperatures. The sodium gluconate dissolved in it is evenly dispersed with the water and adsorbed on the surface of the newly formed hydration products, slowing down the growth rate of ettringite crystals. This provides the mixture with a good working time and ensures a steady increase in the strength of the material after compaction.
[0010] Preferably, the weight parts of each raw material are as follows: 65-75 parts of aged phosphogypsum; 1.5-2.5 parts of ferrous sulfate heptahydrate; 0.3-0.6 parts of sodium fluorosilicate; 0.05-0.1 parts of manganese sulfate monohydrate; 23-30 parts of heat-cured dry powder; and 5-9 parts of quenching conditioning liquid.
[0011] By adopting the above technical solution, the ratio range is derived based on thermal balance calculations and rheological property control. The amount of heat-cured dry powder directly determines the peak temperature rise of the system. If it is too low, the thermal etching reaction cannot be initiated, and if it is too high, it may lead to poor volume stability. The amount of quenching conditioning liquid must be matched with the heat generated by the heat shock to ensure that the final discharge temperature falls back to a suitable range.
[0012] Preferably, the heat-cured dry powder is made from raw materials comprising the following parts by weight: 8-10 parts of highly active quicklime powder; 15-20 parts of slag powder.
[0013] By adopting the above technical solution, quicklime is used as a heat source and alkaline activator, and slag is used as the main cementing component. The premixing of the two can avoid excessively high local concentrations of a single component. Under high-temperature activation, the calcium hydroxide generated by the hydration of quicklime reacts rapidly with the active silica-alumina components depolymerized from the slag to form a dense hydrated calcium silicate gel network, which significantly improves the early strength of the base layer.
[0014] Preferably, the quenching conditioning solution is made from raw materials comprising the following parts by weight: 0.08-0.12 parts sodium gluconate; 5-8 parts industrial water.
[0015] By adopting the above technical solution, the retarding component is pre-dissolved in water and added in the form of atomization, which solves the problem of difficult dispersion of trace admixtures in dry and hard mixtures and avoids the phenomenon of excessive or insufficient local retarding.
[0016] Preferably, the preparation steps of the heat-cured dry powder are as follows: put highly active quicklime powder and slag powder into a dry powder mixer, mix and stir for 3-5 minutes in a dry environment until uniform, and then seal and package.
[0017] By adopting the above technical solution, the premixing treatment in a dry environment can prevent calcium oxide from reacting with moisture in the air in advance, thus ensuring its chemical activity and exothermic capacity when it enters the machine.
[0018] Preferably, the preparation steps of the rapid cooling conditioning solution are as follows: add sodium gluconate to industrial water, turn on mechanical stirring at a speed of 100-200 r / min, and continue stirring for 2-5 min until the solid is completely dissolved to obtain a clear liquid.
[0019] By adopting the above technical solution, the solute is completely dissolved to form a homogeneous system, which is beneficial for forming droplets with uniform particle size during spraying and improving the heat exchange efficiency between the gas and liquid phases.
[0020] Preferably, in step S1, the mixing speed is 40-50 r / min, the mixing time is 60-90 s, and the pH value of the mixed system is about 3.0.
[0021] By adopting the above technical solution, the mild stirring conditions are sufficient to utilize the moisture contained in the raw materials to complete the dissolution of salts and surface wetting. The pH value is controlled at around 3.0 in order to maximize the dissociation of insoluble impurities adsorbed on the surface without damaging the phosphogypsum crystal skeleton.
[0022] Preferably, in step S2, the high-speed shear mixing speed is 80-100 r / min, and the reaction duration is 180-300 s; the heat released by the hydration of the heat-cured dry powder raises the slurry temperature to above 70°C within 120 s.
[0023] By adopting the above technical solution, the mechanical energy input by high-speed shearing helps to break the agglomerated structure of phosphogypsum and increase the solid-liquid contact area; controlling the heating rate to reach above 70°C within 120s is to enable the reaction system to quickly cross the activation energy barrier of the chemical reaction and ensure that the oxidation of impurities and the etching reaction of slag proceed simultaneously and efficiently.
[0024] Preferably, in step S3, the spray pressure of the high-pressure injection is 0.6-1.0 MPa; at the same time, the stirring speed is reduced to 40-50 r / min, and stirring is continued for 120-180 s to reduce the slurry temperature to 38℃-45℃.
[0025] By adopting the above technical solutions, higher spray pressure can significantly increase the specific surface area of droplets and enhance the heat and mass transfer process; reducing the stirring speed is to reduce mechanical disturbance to the initial gel structure that has been formed, while allowing the slurry temperature to smoothly transition to the appropriate paving temperature range.
[0026] Preferably, the high-activity quicklime powder has an effective calcium oxide content ≥85.0%, an activity level (T60) ≤1.5 min, and a fineness of ≤10% residue on a 120-mesh sieve; the slag powder is S95 grade granulated blast furnace slag powder with a specific surface area ≥420 m². 2 / kg.
[0027] By adopting the above technical solution and strictly limiting the activity level (T60) of quicklime, it is crucial to ensure the formation of the "instantaneous high-temperature field." If the activity level is insufficient, the exothermic process will be gradual, and the threshold temperature for thermochemical activation cannot be reached. High specific surface area slag powder provides ample reaction interfaces, which is beneficial for the rapid formation of cementitious products after thermal etching.
[0028] This invention provides a method for preparing a modified phosphogypsum base material for road engineering. It has the following beneficial effects: 1. This invention utilizes the chemical energy released by the hydration of quicklime to construct a high-temperature strong alkali reaction field. Under the catalysis of manganese ions, soluble phosphorus and fluorine impurities in phosphogypsum are converted in situ into insoluble iron complex precipitates, achieving deep mineralization of impurities and reconstruction of the cementitious material network. This significantly improves the water stability and mechanical properties of the base material. Existing technologies often use physical admixture of cement or room-temperature alkali activation, which often suffers from strong impurity shielding effects and weak interfacial adhesion. This solution effectively solves the problems of slow early strength development and easy efflorescence in traditional modified materials.
[0029] 2. This invention utilizes a high-temperature environment to accelerate the hydrolysis of sodium fluorosilicate, and in conjunction with high alkalinity, performs thermal etching on the glassy structure of slag micropowder. This destroys the dense aluminosilicate protective layer on the slag surface, rapidly exposing highly active reaction sites inside, and promoting the formation of dense hydrated calcium silicate gel. Addressing the problems of low potential activity activation efficiency and reliance on long-term curing in conventional cold-mixing processes, this method significantly improves the reaction kinetic rate through the thermal shock effect, overcoming the shortcomings of material hardening lag under low-temperature conditions.
[0030] 3. This invention introduces a conditioning liquid containing retarding components for high-pressure atomization and rapid cooling treatment. It utilizes the latent heat of vaporization to quickly reduce the peak temperature of the material and regulate the crystal growth morphology of the hydration products. This precisely blocks the risk of false setting caused by heat accumulation and inhibits microcracks caused by the malignant expansion of ettringite crystals. Compared with the traditional quicklime activation technology, which suffers from poor workability and insufficient volume stability of the mixture after compaction due to the difficulty in controlling heat release, this technology ensures good workability of the mixture during transportation and paving and crack resistance and durability after compaction. Attached Figure Description
[0031] Figure 1 The graph shows a comparison of the mechanical properties and water stability test results of the test examples of the present invention, where (a) is a comparison of the unconfined compressive strength after 7 days and 28 days, and (b) is a comparison of the water stability coefficient. Figure 2 This is a comparison graph of the free expansion rate curves of the test examples of the present invention as a function of maintenance age; Figure 3 This is a comparison chart of phosphorus and fluorine leaching toxicity concentrations in materials prepared under different process conditions in the test examples of this invention. Figure 4 The figures show the temperature rise curves and solidification times of the stirring process under different processes in the test examples of this invention. (a) is the temperature change curve of the reaction system over time, and (b) is a comparison of the initial solidification time and the final solidification time. Detailed Implementation
[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0034] Aged phosphogypsum: Taken from the stockpile of phosphate fertilizer plant, naturally aged for more than 3 months, the main component is calcium sulfate dihydrate, pH value is 2.5, the water content of the attached water is 12%, the content of soluble phosphorus (calculated as P2O5) in the attached water is 0.35%, the content of soluble fluorine is 0.12%, and the particle size is controlled to be less than 2mm after crushing and screening.
[0035] High-activity quicklime powder: The main component is calcium oxide (CAS No. 1305-78-8), with an effective calcium oxide content ≥85.0%, an activity (T60) of 1.5 min, and a fineness of ≤10% residue on a 120-mesh sieve.
[0036] Slag powder: S95 grade granulated blast furnace slag powder, specific surface area ≥420m² 2 / kg, density ≥2.85g / cm³ 3 The activity index is ≥75% after 7 days.
[0037] Chemical reagents: Ferrous sulfate heptahydrate (CAS No. 7782-63-0, purity ≥98.0%); Sodium fluorosilicate (CAS No. 16893-85-9, purity ≥98.5%, fineness ≤5% on 200-mesh sieve); Manganese sulfate monohydrate (CAS No. 10034-96-5, purity ≥98.0%); Sodium gluconate (CAS No. 527-07-1, purity ≥99.0%).
[0038] Preparation Example 1: This preparation example provides a method for preparing heat-cured dry powder, including the following steps: Weigh 10 kg of highly active quicklime powder and 15 kg of slag powder, put them into a dry powder mixer, and mix and stir for 3-5 minutes at a speed of 40-60 r / min until the materials are evenly mixed to obtain heat-cured dry powder. Seal the package to prevent moisture absorption.
[0039] Preparation Example 2: This preparation example provides a method for preparing heat-cured dry powder, including the following steps: Weigh 9 kg of highly active quicklime powder and 18 kg of slag powder, put them into a dry powder mixer, and mix and stir for 3-5 minutes at a speed of 40-60 r / min until the materials are evenly mixed to obtain heat-cured dry powder. Seal the package to prevent moisture absorption.
[0040] Preparation Example 3: This preparation example provides a method for preparing heat-cured dry powder, including the following steps: Weigh 8 kg of highly active quicklime powder and 20 kg of slag powder, put them into a dry powder mixer, and mix and stir for 3-5 minutes at a speed of 40-60 r / min until the materials are evenly mixed to obtain heat-cured dry powder. Seal the package to prevent moisture absorption.
[0041] Preparation Example 4: This preparation example provides a method for preparing a rapid cooling conditioning solution, including the following steps: Weigh 0.10 kg of sodium gluconate and add it to 6 kg of industrial water. Turn on the mechanical stirrer at room temperature and stir at a speed of 100-200 r / min for 2-5 minutes until the solid is completely dissolved, and a clear and transparent quenched conditioning solution is obtained.
[0042] Preparation Example 5: This preparation example provides a method for preparing a rapid cooling conditioning solution, including the following steps: Weigh 0.12 kg of sodium gluconate and add it to 5 kg of industrial water. Turn on the mechanical stirrer at room temperature and stir at a speed of 100-200 r / min for 2-5 minutes until the solid is completely dissolved, and a clear and transparent quenched conditioning solution is obtained.
[0043] Preparation Example 6: This preparation example provides a method for preparing a rapid cooling conditioning solution, including the following steps: Weigh 0.08 kg of sodium gluconate and add it to 8 kg of industrial water. Turn on the mechanical stirrer at room temperature and stir at a speed of 100-200 r / min for 2-5 minutes until the solid is completely dissolved, and a clear and transparent quenched conditioning solution is obtained.
[0044] Example 1: This embodiment provides a method for preparing a modified phosphogypsum base material for road engineering, including the following steps: (1) 70 kg of aged phosphogypsum, 2.0 kg of ferrous sulfate heptahydrate, 0.45 kg of sodium fluorosilicate and 0.08 kg of manganese sulfate monohydrate were put into a twin-shaft forced mixer and stirred for 60 s at a speed of 45 r / min. The salts were dissolved by the water contained in the phosphogypsum. At this time, the pH value of the system was about 3.0.
[0045] (2) Keep stirring and put all the heat-cured dry powder obtained in Example 2 into the mixer at once. Immediately increase the stirring speed to 90 r / min for high-speed shear mixing. The reaction lasts for 240 s. During this period, the hydration heat of quicklime is used to raise the slurry temperature to 75°C within 120 s and initiate the manganese catalytic oxidation reaction. The color of the material gradually changes from grayish-white to reddish-brown.
[0046] (3) After the reaction in step (2) is completed, all the quenching and conditioning liquid obtained in Preparation Example 4 is immediately sprayed into the mixer through a high-pressure atomizing nozzle. The spray pressure is 0.8 MPa. At the same time, the stirring speed is reduced to 45 r / min and stirring is continued for 150 s. The latent heat of water evaporation is used to rapidly reduce the temperature of the slurry to 42°C, thus completing the quenching and slow solidification locking.
[0047] (4) The mixture is unloaded and transported to the stockpile, covered with a moisture-retaining cloth and aged for 24 hours to obtain the modified phosphogypsum base material.
[0048] Example 2: This embodiment provides a method for preparing a modified phosphogypsum base material for road engineering, including the following steps: (1) Put 65kg of aged phosphogypsum, 2.5kg of ferrous sulfate heptahydrate, 0.6kg of sodium fluorosilicate and 0.1kg of manganese sulfate monohydrate into a twin-shaft forced mixer and stir for 60s at a speed of 50r / min until they are evenly mixed.
[0049] (2) Keep stirring and put all the heat-cured dry powder obtained in Preparation Example 1 into the mixer at once. Immediately increase the stirring speed to 100 r / min. The reaction lasts for 300 s and the peak temperature of the slurry rises to 85°C. High temperature is used to promote the deep thermal etching of sodium fluorosilicate on the slag glass.
[0050] (3) After the reaction in step (2) is completed, immediately spray all the rapid cooling conditioning liquid obtained in Preparation Example 5 into the solution at a spray pressure of 1.0 MPa; reduce the stirring speed to 40 r / min and continue stirring for 180 s to rapidly reduce the temperature of the slurry to below 45°C.
[0051] (4) The mixture is unloaded and transported to the stockpile, covered with a moisture-retaining cloth and aged for 24 hours to obtain the modified phosphogypsum base material.
[0052] Example 3: This embodiment provides a method for preparing a modified phosphogypsum base material for road engineering, including the following steps: (1) Put 75kg of aged phosphogypsum, 1.5kg of ferrous sulfate heptahydrate, 0.3kg of sodium fluorosilicate and 0.05kg of manganese sulfate monohydrate into a twin-shaft forced mixer and stir for 90s at a speed of 40r / min until they are evenly mixed.
[0053] (2) Keep stirring and put all the heat-cured dry powder obtained in Preparation Example 3 into the mixer at once, and immediately increase the stirring speed to 80 r / min; the reaction lasts for 180 s and the peak temperature of the slurry rises to 65 ℃.
[0054] (3) After the reaction in step (2) is completed, immediately spray all the rapid cooling conditioning liquid obtained in Preparation Example 6 into the mixture at a spray pressure of 0.6 MPa; reduce the stirring speed to 50 r / min and continue stirring for 120 s to rapidly reduce the temperature of the slurry to 38°C.
[0055] (4) The mixture is unloaded and transported to the stockpile, covered with a moisture-retaining cloth and aged for 12 hours to obtain the modified phosphogypsum base material.
[0056] Example 4: This embodiment provides a method for preparing a modified phosphogypsum base material for road engineering, including the following steps: (1) 70 kg of aged phosphogypsum, 2.0 kg of ferrous sulfate heptahydrate, 0.45 kg of sodium fluorosilicate and 0.06 kg of manganese sulfate monohydrate were put into a twin-shaft forced mixer and stirred for 60 s at a speed of 45 r / min.
[0057] (2) Keep stirring and put all the heat-cured dry powder obtained in Preparation Example 2 into the mixer at once, and immediately increase the stirring speed to 90 r / min; the reaction lasts for 240 s and the peak temperature of the slurry reaches 74 ℃.
[0058] (3) After the reaction in step (2) is completed, immediately spray all the rapid cooling conditioning liquid obtained in Preparation Example 4 into the mixture at a spray pressure of 0.8 MPa; reduce the stirring speed to 45 r / min and continue stirring for 150 s to rapidly reduce the temperature of the slurry to 41 °C.
[0059] (4) The mixture is unloaded and transported to the stockpile, covered with a moisture-retaining cloth and aged for 24 hours to obtain the modified phosphogypsum base material.
[0060] Example 5: This embodiment provides a method for preparing a modified phosphogypsum base material for road engineering, including the following steps: (1) 72 kg of aged phosphogypsum, 1.8 kg of ferrous sulfate heptahydrate, 0.5 kg of sodium fluorosilicate and 0.09 kg of manganese sulfate monohydrate were put into a twin-shaft forced mixer and stirred for 60 s at a speed of 45 r / min.
[0061] (2) Keep stirring and put all the heat-cured dry powder obtained in Preparation Example 2 into the mixer at once, and immediately increase the stirring speed to 95 r / min; the reaction lasts for 200 s and the peak temperature of the slurry reaches 78℃.
[0062] (3) After the reaction in step (2) is completed, immediately spray all the rapid cooling conditioning liquid obtained in Preparation Example 4 into the mixture. The spray pressure is 0.9 MPa. Reduce the stirring speed to 45 r / min and continue stirring for 140 s to rapidly reduce the temperature of the slurry to 43 °C.
[0063] (4) The mixture is unloaded and transported to the stockpile, covered with a moisture-retaining cloth and aged for 20 hours to obtain the modified phosphogypsum base material.
[0064] Comparative Example 1: Compared with Example 1, the difference is that 9 kg of highly active quicklime powder in the heat-cured dry powder was replaced with 11.9 kg of calcium hydroxide powder, and the mixing process was carried out at room temperature without using the heat of hydration to raise the system temperature. All other aspects are the same.
[0065] Comparative Example 2: Compared with Example 1, the difference is that in step 3, the high-pressure atomized spray of the quenching conditioning liquid was not used for forced cooling. Instead, the quenching conditioning liquid was directly injected into the mixer and then naturally stirred and cooled. The goal of rapidly reducing the slurry temperature to below 45°C within 2 minutes was not achieved. All other aspects are the same.
[0066] Comparative Example 3: Compared with Example 1, the difference is that manganese sulfate monohydrate was not added to the raw materials in step 1, but all other aspects are the same.
[0067] Comparative Example 4: Compared with Example 1, the difference is that the pre-preparation step of heat-cured dry powder is omitted. In step 2, 9 kg of highly active quicklime powder is directly added to wet phosphogypsum, followed by 18 kg of slag powder. The solid pre-dispersion of quicklime and slag powder is not achieved. All other aspects are the same.
[0068] Comparative Example 5: Compared with Example 1, the difference lies in the change of the feeding sequence. All raw materials, including aged phosphogypsum, ferrous sulfate heptahydrate, sodium fluorosilicate, manganese sulfate monohydrate, heat-cured dry powder, and quenching conditioning liquid, are added to the mixer at once for mixing. Stepwise reaction control is not performed. All other aspects are the same.
[0069] Test Example 1: Test objective: To verify the basic mechanical properties and water stability of the modified phosphogypsum base material prepared by this invention for road use, and to compare it with existing technologies and non-stepping processes.
[0070] Experimental steps: 1. Fresh mixtures were prepared according to the formulation ratios and preparation processes described in Examples 1 to 5, and Comparative Examples 1 and 5.
[0071] 2. Referring to the static compaction method in JTG E51-2009 "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering", the mixture was prepared into cylindrical specimens with a diameter of 150 mm and a height of 150 mm, and the compaction degree was uniformly controlled at 98%. 18 parallel specimens were prepared for each formula, divided into three groups of 6 specimens each.
[0072] 3. Place the molded specimens in a standard curing room for curing, with the temperature controlled at 20±2℃ and the relative humidity maintained above 95%.
[0073] 4. The first group of specimens underwent a 7-day unconfined compressive strength test. The curing method was standard curing for 6 days, followed by immersion in water for 24 hours. After removing and drying the surface moisture, the pressure test was immediately conducted, with the loading rate controlled at 1 mm / min.
[0074] 5. The second group of specimens underwent an unconfined compressive strength test after 28 days. The curing method was standard curing for 27 days, followed by immersion in water for 24 hours. The testing method was the same as above.
[0075] 6. The third group of specimens was used to determine the water stability coefficient. After 28 days of standard curing, the specimens were not immersed in water; their dry strength was tested directly. The formula for calculating the water stability coefficient is: the ratio of the immersion strength to the non-immersion strength at the same age (28 days).
[0076] The experimental data are shown in Table 1: Table 1: Road performance test results of each embodiment and comparative example
[0077] Note: The data in the table are the arithmetic mean of 6 parallel specimens after removing outliers.
[0078] Experimental conclusion: According to Table 1 and Figure 1 Data analysis shows that Examples 1 to 5, prepared using the thermochemical coupling process described in this invention, are significantly superior to the comparative examples in terms of mechanical properties and water stability. The 7-day unconfined compressive strength of the example groups generally reaches over 3.4 MPa, and the 28-day strength exceeds 5.9 MPa, fully meeting the strength requirements for heavy traffic road base courses in the Ministry of Transport standard JT / T 1551-2025. This high strength is mainly attributed to the efficient operation of the manganese-catalyzed thermo-oxidation mechanism. Through the instantaneous high-temperature field and strong alkaline environment generated by quicklime hydration, combined with the electron transfer effect of manganese ions, the ferrous ions on the surface of phosphogypsum are rapidly oxidized and transformed into iron-based gels with gelling activity. Simultaneously, the retardation interference of phosphorus and fluorine impurities on the hydration of the cementitious material is eliminated, allowing the hydration reaction to proceed rapidly in the early stages.
[0079] Comparative Example 1 showed the worst performance, with a 7-day strength of only 1.43 MPa and a water stability coefficient as low as 55.0%. This indicates that, in the absence of thermal activation and manganese catalysis, the acidic impurities in phosphogypsum severely hindered the normal hydration of cement minerals, resulting in a loose microstructure that easily disintegrated upon contact with water. The water stability coefficients of the example groups remained above 88%, with some reaching 92%, strongly confirming the effectiveness of the thermal etching mechanism. High temperature induced the decomposition of sodium fluorosilicate, generating acidic fluoride ions that etched the slag glass in situ. The exposed active silicon-aluminum sites formed a dense interpenetrating crystal-colloid network with the subsequently generated CSH gel and iron colloid, significantly improving the interfacial bonding strength of the material in an aqueous environment.
[0080] Comparing Example 1 and Comparative Example 5, it can be seen that even with identical raw material formulations, the 7-day strength of the material decreased by approximately 46% and the water stability coefficient was only 70.9% when using the traditional "one-pot" mixing process. This indicates that a specific feeding sequence is crucial to achieving the technical effects of this invention. The step-by-step process ensured that the chemical reaction pathway of "acidic complexation first, then alkaline thermal shock, and finally rapid cooling and locking" was not disrupted. In Comparative Example 5, due to the lack of independent acidic pretreatment and a controlled thermal shock stage, impurities were not thoroughly solidified, and the premature introduction of sodium gluconate may have interfered with the initial activation of the slag, resulting in a significant reduction in the strength and durability of the final structure. Example 2 achieved optimal mechanical properties at a higher reaction temperature, further verifying the positive effect of a moderate high-temperature thermal field on activating the potential activity of the slag and enhancing the density of the matrix.
[0081] Test Example 2: Test objective: To verify the effect of rapid quenching process on the volume stability of modified phosphogypsum base material through comparative experiments, with a focus on examining the actual effectiveness of the "phase change cycle and rapid quenching lock" mechanism in suppressing the risk of later expansion.
[0082] Experimental steps: 1. Example 1 and Comparative Example 2 were selected as experimental subjects. The only difference between the two is that Example 1 used high-pressure atomization rapid cooling conditioning liquid for forced cooling, while Comparative Example 2 only underwent natural cooling and stirring after the thermal reaction.
[0083] 2. Referring to the test principles in GB / T 17669.4-1999 "Determination of Physical Properties of Building Gypsum Paste" and GB 50119-2013 "Technical Specification for Application of Concrete Admixtures", the volume change of the hardened paste was monitored using the dial gauge method. Cylindrical specimens with a diameter of 150 mm and a height of 150 mm were formed using the prepared fresh mixture, and the compaction degree was controlled at 98%.
[0084] 3. Before demolding the molded specimen, install a brass probe at the center of the top surface of the specimen, place the specimen on a porous permeable plate, and put it in a constant temperature and humidity curing chamber. Set the curing temperature to 20±2℃ and maintain the relative humidity above 95% to prevent uncontrolled evaporation of moisture.
[0085] 4. Set up a high-precision dial indicator on the top surface of the specimen and record the initial reading as d0. Then, read the dial indicator values at 7 days and 28 days of curing. During this period, check the smooth movement of the dial indicator probe regularly and record the dial indicator reading at each time point.
[0086] 5. Calculate the free expansion rate at different ages based on the ratio of the change in dial gauge reading to the initial height of the specimen, in order to evaluate the volume change trend of the material during the hardening process. Take the arithmetic mean of 3 specimens for each formulation as the final test result.
[0087] The experimental data are shown in Table 2: Table 2: Volume stability test results of the examples and comparative examples
[0088] Experimental conclusion: According to Table 2 and Figure 2 The test data showed that Example 1 and Comparative Example 2 exhibited drastically different evolution trajectories in terms of volume stability. Example 1 maintained an extremely low expansion rate throughout the entire 28-day curing period, with a final expansion rate of only 0.12% after 28 days, far below the 0.6% limit typically required for road base materials, demonstrating excellent volume stability. Comparative Example 2, on the other hand, showed an exponential increase in expansion rate over time, reaching 0.94% after 7 days and a staggering 2.67% after 28 days; even visible microcracks were observed on the surface of the specimen.
[0089] This significant difference profoundly reveals the decisive role of the rapid quenching process in the technical system of this invention. During the thermal activation stage, the exothermic hydration of quicklime raises the system temperature, causing partial dehydration of the dihydrate calcium sulfate on the phosphogypsum surface, transforming it into hemihydrate calcium sulfate. Example 1, by introducing a rapid quenching conditioning solution containing sodium gluconate at the peak of the reaction, utilizes the latent heat of vaporization of water to rapidly lower the material temperature below 45°C. This operation creates a water-rich and low-temperature environment inside the mixer, forcing the newly formed hemihydrate gypsum to rapidly absorb water in situ before the cementitious skeleton hardens, reverting to dihydrate gypsum. This means that the potential chemical expansion energy is completely consumed during the mixing stage, thus achieving closed-loop locking of the phase transition.
[0090] In Comparative Example 2, due to the lack of a forced quenching step, the material cooled slowly and naturally at a higher temperature. This resulted in a large amount of hemihydrate gypsum generated during the high-temperature stage failing to revert in time and remaining in the matrix. During subsequent curing and use, this residual hemihydrate gypsum slowly absorbs environmental moisture and transforms into dihydrate gypsum, a process accompanied by an increase in solid volume of approximately 60%. Since the cementitious material skeleton has already formed and possesses a certain strength at this point, the internal crystal growth stress cannot be released, ultimately leading to drastic macroscopic volume expansion and structural damage. Furthermore, the introduction of sodium gluconate into the quenching liquid also inhibited disordered crystal growth at the microscopic level, further assisting in the control of volume stability and ensuring the dimensional accuracy and structural integrity of the material throughout its entire life cycle in road engineering projects.
[0091] Test Example 3: Test objective: To verify the curing efficiency of the manganese catalytic thermal oxidation system on soluble impurities in phosphogypsum from two dimensions: microscopic chemical reaction mechanism and macroscopic environmental indicators. The focus is on examining the synergistic effect of the thermal field and catalyst in the oxidation of ferrous ions and the curing of phosphorus and fluorine.
[0092] Experimental steps: 1. The mixtures prepared in Example 1, Comparative Example 1, and Comparative Example 3 were selected as the observation objects. Immediately after the mixer was discharged, the appearance and color of the fresh mixture were visually evaluated and recorded to serve as an intuitive basis for judging the valence state and oxidation degree of iron.
[0093] 2. Prepare cubic specimens of 100mm×100mm×100mm from the three mixtures mentioned above, and cure them under standard conditions for 7 days. Then crush the specimens and collect particles with a diameter less than 9.5mm as the test samples.
[0094] 3. Operate according to HJ 557-2010 "Leaching Toxicity of Solid Waste - Horizontal Oscillation Method", weigh 100g of the sample to be tested and place it in a 2L extraction bottle, add deionized water at a liquid-to-solid ratio of 10:1 (L / kg), fix it on a horizontal shaker, adjust the oscillation frequency to 110 times / min, oscillate continuously at room temperature for 8 hours, and then let it stand for 16 hours.
[0095] 4. The supernatant was filtered through a 0.45 μm microporous membrane to obtain the leachate. The concentration of soluble phosphorus (calculated as total phosphorus P) in the leachate was determined using inductively coupled plasma optical emission spectrometry (ICP-OES), and the concentration of soluble fluoride ions (F) was determined using ion chromatography. - The concentration of ).
[0096] 5. Take another set of molded specimens and place them in a natural environment for 28 days for curing. Focus on observing whether there is yellowish-brown "frost" or local spot discoloration on the surface of the specimens due to the slow oxidation and migration of ferrous ions in the later stage, in order to evaluate the long-term stability of impurity curing.
[0097] The experimental data are shown in Table 3: Table 3: Results of Impurity Curing Effect and Environmental Performance Tests
[0098] Experimental conclusion: From Table 3 and Figure 3 The test results show that Example 1 exhibits significant advantages in environmental performance, with phosphorus and fluorine leaching concentrations as low as 0.15 mg / L and 0.82 mg / L, respectively, fully complying with environmental safety standards. This excellent performance is highly consistent with the uniform reddish-brown appearance of the mixture, directly confirming the high efficiency of the manganese catalytic thermal oxidation mechanism. In the high-temperature and strongly alkaline environment provided by quicklime hydration, manganese sulfate, as an electron transport carrier, greatly reduces the activation energy of ferrous ion oxidation, prompting it to rapidly transform into high-valence iron ions within a stirring window of several minutes. The in-situ generated ferric hydroxide colloid has a huge specific surface area and abundant surface hydroxyl groups, which can efficiently adsorb and chemically bond phosphate and fluoride ions like a net, transforming them from a soluble state into a stable inert complex, thereby completely cutting off the path of impurity precipitation.
[0099] The data from Comparative Example 1 presents a stark contrast, with phosphorus and fluoride concentrations in its leachate reaching as high as 4.23 mg / L and 8.65 mg / L, respectively, and the mixture exhibiting a grayish-green color. This indicates that under ambient temperature conditions lacking thermal activation, relying solely on oxygen in the air is insufficient to drive the rapid oxidation of acidic ferrous ions. The large amount of residual ferrous ions not only fails to act as colloidal adsorption but also migrates to the specimen surface with moisture during subsequent natural curing, undergoing delayed oxidation upon encountering oxygen, resulting in the observed yellowish-brown rust spots and efflorescence. Although a heat source was introduced in Comparative Example 3, the phosphorus and fluoride leaching values were still significantly higher than in Example 1 due to the absence of a manganese catalyst. This reveals that thermal activation alone is insufficient to complete the oxidation reaction in a short time; the catalytic intervention of manganese ions plays a decisive role in overcoming kinetic obstacles and ensuring the harmless transformation of impurities before solidification and hardening. This test fully demonstrates that the "heat + alkali + catalysis" ternary coupling strategy proposed in this invention is a necessary and sufficient condition for solving the problem of impurity solidification in phosphogypsum.
[0100] Test Example 4: Test objective: To investigate the thermal safety of the preparation process and the construction adaptability of the slurry, with a focus on verifying the regulatory effect of solid pre-dispersion technology on the intense exothermic reaction of quicklime hydration, and the effect of rapid cooling and slow setting process on extending the construction window period.
[0101] Experimental steps: 1. In the preparation process of Example 1 and Comparative Example 4, K-type thermocouples and infrared thermal imagers embedded inside the mixer were used to monitor the temperature changes throughout the mixing process in real time. The data acquisition frequency was set to once every 5 seconds to record the complete temperature rise curve from the start of feeding to the end of unloading. At the same time, a dedicated person was assigned to observe and record whether there were any abnormal phenomena such as steam gushing, slurry splashing, or dust escape at the mixer opening.
[0102] 2. At the end of the mixing process, collect approximately 5 kg of freshly mixed material. Since the mixture contains coarse aggregate, conduct tests according to the national standard GB / T 1346-2011 "Test Method for Standard Consistency Water Requirement, Setting Time and Soundness of Cement". Immediately after testing, pass the mixture through a 4.75 mm square-hole sieve to remove coarse aggregate and collect the fine particles that pass through the sieve as the test sample.
[0103] 3. Pour the sieved slurry into a circular mold, vibrate and compact it, and scrape the surface smooth before placing it in a curing chamber. Use a standard Vicat apparatus to determine the initial setting time and final setting time. During the test, measure the needle penetration depth every 15 minutes, and shorten this to every 5 minutes as the setting time approaches, until the needle penetration depth meets the final setting requirements specified in the standard. This is used to assess the workable time window of the material during actual construction, transportation, paving, and compaction.
[0104] The experimental data are shown in Table 4: Table 4: Monitoring Data on Process Safety and Construction Performance
[0105] Experimental conclusion: Table 4 and Figure 4 The data clearly reflects the decisive impact of process improvements on production safety and construction performance. The temperature rise curve of Example 1 exhibits a smooth and controllable characteristic, with the peak temperature controlled at 76.2℃ and the peak time delayed to 145 seconds. The entire stirring process was stable and without abnormalities. This safety is achieved through the pre-preparation step of the heat-curing dry powder. The slag micro-powder particles effectively coat and separate the highly reactive quicklime particles, acting as a physical heat sink and dispersion medium. When the mixture encounters water, the heat released by the dispersed quicklime particles is rapidly absorbed by the surrounding slag and evenly transferred to the entire slurry system, avoiding a chain reaction of boiling caused by localized heat accumulation, thereby eliminating the risk of steam splashing and dust explosion.
[0106] In contrast, Comparative Example 4, where quicklime was directly added to the wet aggregate, caused the temperature to surge to 94.8°C within just 55 seconds, approaching the boiling point of water. This triggered violent localized boiling and steam eruption, posing serious production safety hazards and resulting in the loss of some moisture as steam, disrupting the water-cement ratio balance. More seriously, despite the presence of a rapidly cooled conditioning liquid in the system, the lack of solid pre-dispersion meant that the extreme high temperature of 94.8°C generated by quicklime hydration significantly accelerated the gelation reaction kinetics. This thermal acceleration effect far outweighed the retarding and inhibiting ability of sodium gluconate, and may even have caused some organic retarder to become ineffective at high temperatures. Comparative Example 4 exhibited an initial setting time of only 42 minutes, demonstrating a typical "flash setting" phenomenon. This is because the high temperature drastically accelerated the gelation reaction rate, causing the slurry to lose its fluidity before even leaving the mixing plant or immediately after paving, making it impossible to meet the minimum requirements for transportation, paving, and compaction time in road base construction. Example 1 successfully extended the initial setting time to 235 minutes through the dual effects of rapid cooling and chemical retarding, providing ample operating window for on-site construction and ensuring the compaction density and overall strength of the base structure.
[0107] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a modified phosphogypsum base material for road engineering, characterized in that, Includes the following steps: S1. Mix aged phosphogypsum with ferrous sulfate heptahydrate, sodium fluorosilicate and manganese sulfate monohydrate, and use the water in the phosphogypsum to dissolve the salts to form an acidic slurry. S2. Add heat-curing dry powder to the slurry obtained in S1 and perform high-speed shear mixing. Use the heat released by the hydration of the heat-curing dry powder to raise the slurry temperature to 65℃-85℃, creating a high-temperature strong alkaline environment to initiate the manganese catalytic oxidation reaction and thermal etching of the slag. S3. Immediately after the S2 reaction is completed, a rapid cooling conditioning liquid is injected into the mixer under high pressure. The latent heat of water evaporation is used to rapidly reduce the temperature of the slurry to below 45°C, thus completing the rapid cooling quenching and slow setting lock. S4. Discharge and age the mixture to obtain the modified phosphogypsum base material; The weight proportions of each raw material are as follows: Aged phosphogypsum: 65-75 parts; Ferrous sulfate heptahydrate: 1.5-2.5 parts; Sodium fluorosilicate: 0.3-0.6 parts; Manganese sulfate monohydrate: 0.05-0.1 parts; Heat-cured dry powder: 23-30 parts; Rapid cooling conditioning solution: 5-9 parts; The heat-cured dry powder is made from raw materials comprising the following parts by weight: Highly active quicklime powder: 8-10 parts; Slag powder: 15-20 parts; The quenching and conditioning solution is made from raw materials comprising the following parts by weight: Sodium gluconate: 0.08-0.12 parts; Industrial water: 5-8 parts.
2. The method for preparing the modified phosphogypsum base material for road engineering according to claim 1, characterized in that, The preparation steps of the heat-cured dry powder are as follows: put high-activity quicklime powder and slag powder into a dry powder mixer, mix and stir for 3-5 minutes in a dry environment until uniform, and then seal and package.
3. The method for preparing the modified phosphogypsum base material for road engineering according to claim 1, characterized in that, The preparation steps of the rapid cooling conditioning solution are as follows: add sodium gluconate to industrial water, turn on mechanical stirring at a speed of 100-200 r / min, and continue stirring for 2-5 min until the solid is completely dissolved to obtain a clear liquid.
4. The method for preparing the modified phosphogypsum base material for road engineering according to claim 1, characterized in that, In step S1, the mixing speed is 40-50 r / min and the mixing time is 60-90 s.
5. The method for preparing the modified phosphogypsum base material for road engineering according to claim 1, characterized in that, In step S2, the high-speed shear mixing speed is 80-100 r / min, and the reaction duration is 180-300 s; the heat released by the hydration of the heat-cured dry powder raises the slurry temperature to above 70°C within 120 s.
6. The method for preparing the modified phosphogypsum base material for road engineering according to claim 1, characterized in that, In step S3, the spray pressure of the high-pressure injection is 0.6-1.0 MPa; at the same time, the stirring speed is reduced to 40-50 r / min, and stirring is continued for 120-180 s to reduce the slurry temperature to 38℃-45℃.
7. The method for preparing the modified phosphogypsum base material for road engineering according to claim 1, characterized in that, The high-activity quicklime powder has an effective calcium oxide content ≥85.0%, an activity level (T60) ≤1.5 min, and a fineness of ≤10% residue on a 120-mesh sieve; the slag powder is S95 grade granulated blast furnace slag powder with a specific surface area ≥420 m². 2 / kg.
Citation Information
Patent Citations
Process for low-carbon all-component synergistic utilization of industrial solid wastes of high-iron red mud and coal gangue
CN118515444A
Phosphogypsum road base material and preparation method thereof
CN119430836A